Answer:
b= 2 is the solution for the given equation.
Explanation:
Here, the given expression is:
Simplifying Left side, we get
=
![(7(b-3) + 5(b+3))/((b+3)(b-3))](https://img.qammunity.org/2020/formulas/mathematics/high-school/cti3hx2phalyg436kyaigg847y0ll8zgos.png)
Also, by ALGEBARIC IDENTITY:
![x^(2) -y^(2) = (x+y)(x-y)](https://img.qammunity.org/2020/formulas/mathematics/high-school/1eo9y887dp93n4wbtwjtehfc5snunn5bv5.png)
So,
![(b+3)(b-3) = b^(2) -9](https://img.qammunity.org/2020/formulas/mathematics/high-school/mdq7jd58nnf2x623hcsfuotil8sond92q8.png)
So, LHS becomes
![(7(b-3) + 5(b+3))/(b^(2) -9)](https://img.qammunity.org/2020/formulas/mathematics/high-school/djamvibp8q3drnx7s2dcog19dak9x7gs93.png)
Compare both Left side, Right side we get
=
or, 7(b-3) + 5(b+3) = 10b -2
⇒ 7b - 21 + 5b + 15 = 10b -2
or, 12b - 10b = 6-2
or, 2b = 4 ⇒ b = 4/2 = 2
⇒ b= 2 is the solution for the given equation.